Electrochemical studies of seven regioisomers of tris[di(ethoxycarbonyl)methanol][60]fullerence: Umpolung of regiochemistry in retro-bingel reactions and walk-on-the-sphere rearrangements - Echegoyen, Lourdes E.; Djojo, Francis; Hirsch, Andreas; Echegoyen, Luis (Journal of Organic Chemistry, 2000)
Seven of the possible 46 constitutional isomers of tris[di(ethoxycarbonyl)methano[60]fullerene have been isolated and their electrochemical properties studied in CH Cl . A two-electron controlled potential electrolysis of each of these isomers results in competing retro-Bingel and isomerization reactions with preferential loss of one or two of the addends. PM3 and AM1 computational studies indicate that while the reactivity of neutral precursors is kinetically controlled, charging of the neutral species with two electrons results in an umpolung of reactivity and introduction of thermodynamic control. Lowering the electrolysis temperature increases the proportion of isomerization, and a new tris-isomer never obtained before via synthetic methods has been isolated.